On the rig dock tuning of large sail yachts. (1st July 2019) - Ghelardi, Stefano; Garavaglia, Alessandra; Rizzo, Cesare Mario; Paci, Matteo
Abstract: Dock tuning is a crucial stage in the rig service life and in the sailing management. Such operation is necessary for safety and structural stability reasons. The applied pretension has the purpose to increase the stiffness of the whole rig, reducing large displacements caused by aerodynamic and inertial loads. Furthermore, since the rig is aimed at supporting sails, its deformation significantly affects aerodynamic performances, so that dock tuning has also a relevant impact on the propulsion, especially in racing. However, the complexity of the problem and the peculiarities of each different system are the causes of the lack of specific dock tuning procedures in rules and guidelines of Classification societies. The present work, developed in collaboration with the Italian shipyard Perini Navi S.p.A., consists in the validation of a dock tuning numerical procedure adopting a Finite Element Method (FEM) applied to a 67 m long mast. A detailed comparison with real-scale experimental results has been carried out, highlighting the importance of a reliable modelling to accurately predict the non-linear behaviour of the structure. Technical guidelines for dock tuning simulation of large rigs are also provided for the first time in open literature, to the best of the authors' knowledge. Highlights: Dock tuning: a crucial stage in the rig service life and in the sailing management for safety and performances reasons. No detailed procedures are specified in technical guidelines of Classification societies. A common experimental dock tuning procedure on a large sail yacht rig is reported. Numerical procedures validated via FEA, highlighting the importance of modelling internal reinforcements and filler. Technical guidelines for rig dock tuning simulations are provided.